Hall-effect measurements of metalorganic vapor-phase epitaxy-grown p-type homoepitaxial GaN layers with various Mg concentrations. (17th February 2017) - Horita, Masahiro; Takashima, Shinya; Tanaka, Ryo; Matsuyama, Hideaki; Ueno, Katsunori; Edo, Masaharu; Takahashi, Tokio; Shimizu, Mitsuaki; Suda, Jun
Abstract: Mg-doped p-type gallium nitride (GaN) layers with doping concentrations in the range from 6.5 × 10 16 cm −3 (lightly doped) to 3.8 × 10 19 cm −3 (heavily doped) were investigated by Hall-effect measurement for the analysis of hole concentration and mobility. p-GaN was homoepitaxially grown on a GaN free-standing substrate by metalorganic vapor-phase epitaxy. The threading dislocation density of p-GaN was 4 × 10 6 cm −2 measured by cathodoluminescence mapping. Hall-effect measurements of p-GaN were carried out at a temperature in the range from 130 to 450 K. For the lightly doped p-GaN, the acceptor concentration of 7.0 × 10 16 cm −3 and the donor concentration of 3.2 × 10 16 cm −3 were obtained, where the compensation ratio was 46%. We also obtained the depth of the Mg acceptor level to be 220 meV. The hole mobilities of 86, 31, 14 cm 2 V −1 s −1 at 200, 300, 400 K, respectively, were observed in the lightly doped p-GaN.